Longitudinal trends in causes of death among adults with HIV on antiretroviral therapy in Europe and North America from 1996 to 2020: a collaboration of cohort studies - Trickey, Adam; McGinnis, Kathleen; Gill, M John; Abgrall, Sophie; Berenguer, Juan; Wyen, Christoph; Hessamfar, Mojgan; Reiss, Peter; Kusejko, Katharina; Silverberg, Michael J; Imaz, Arkaitz; Teira, Ramon; et al. (The lancet HIV, 2024)
Mortality rates among people with HIV have fallen since 1996 following the widespread availability of effective antiretroviral therapy (ART). Patterns of cause-specific mortality are evolving as the population with HIV ages. We aimed to investigate longitudinal trends in cause-specific mortality among people with HIV starting ART in Europe and North America. In this collaborative observational cohort study, we used data from 17 European and North American HIV cohorts contributing data to the Antiretroviral Therapy Cohort Collaboration. We included data for people with HIV who started ART between 1996 and 2020 at the age of 16 years or older. Causes of death were classified into a single cause by both a clinician and an algorithm if International Classification of Diseases, Ninth Revision or Tenth Revision data were available, or independently by two clinicians. Disagreements were resolved through panel discussion. We used Poisson models to compare cause-specific mortality rates during the calendar periods 1996-99, 2000-03, 2004-07, 2008-11, 2012-15, and 2016-20, adjusted for time-updated age, CD4 count, and whether the individual was ART-naive at the start of each period. Among 189 301 people with HIV included in this study, 16 832 (8·9%) deaths were recorded during 1 519 200 person-years of follow-up. 13 180 (78·3%) deaths were classified by cause: the most common causes were AIDS (4203 deaths; 25·0%), non-AIDS non-hepatitis malignancy (2311; 13·7%), and cardiovascular or heart-related (1403; 8·3%) mortality. The proportion of deaths due to AIDS declined from 49% during 1996-99 to 16% during 2016-20. Rates of all-cause mortality per 1000 person-years decreased from 16·8 deaths (95% CI 15·4-18·4) during 1996-99 to 7·9 deaths (7·6-8·2) during 2016-20. Rates of all-cause mortality declined with time: the average adjusted mortality rate ratio per calendar period was 0·85 (95% CI 0·84-0·86). Rates of cause-specific mortality also declined: the most pronounced reduction was for AIDS-related mortality (0·81; 0·79-0·83). There were also reductions in rates of cardiovascular-related (0·83, 0·79-0·87), liver-related (0·88, 0·84-0·93), non-AIDS infection-related (0·91, 0·86-0·96), non-AIDS-non-hepatocellular carcinoma malignancy-related (0·94, 0·90-0·97), and suicide or accident-related mortality (0·89, 0·82-0·95). Mortality rates among people who acquired HIV through injecting drug use increased in women (1·07, 1·00-1·14) and decreased slightly in men (0·96, 0·93-0·99). Reductions of most major causes of death, particularly AIDS-related deaths among people with HIV on ART, were not seen for all subgroups. Interventions targeted at high-risk groups, substance use, and comorbidities might further increase life expectancy in people with HIV towards that in the general population. US National Institute on Alcohol Abuse and Alcoholism.